Self-forming actions, contrastive explanations, and the structure of the will. - Campbell, Neil (Synthese, 2020)
Robert Kane's libertarian theory is often attacked on the grounds that undetermined self-forming actions are not amenable to contrastive explanation. I propose that we should understand contrastive explanations in terms of an appeal to structuring causes. Doing so reveals that Kane's claim that there can be no contrastive explanation for self-forming actions is not an unwanted implication of his appeal to indeterminism, but is actually an implication of the fact that the agent's will is not yet appropriately structured. I then explain how this can assist Kane with the luck objection.